New advances in targeting aberrant signaling pathways in T-cell acute lymphoblastic leukemia. (December 2019) - Paganelli, Francesca; Lonetti, Annalisa; Anselmi, Laura; Martelli, Alberto M.; Evangelisti, Camilla; Chiarini, Francesca
Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive disorder characterized by malignant transformation of immature progenitors primed towards T-cell development. Over the past 15 years, advances in the molecular characterization of T-ALL have uncovered oncogenic key drivers and crucial signaling pathways of this disease, opening new chances for the development of novel therapeutic strategies. Currently, T-ALL patients are still treated with aggressive therapies, consisting of high dose multiagent chemotherapy. To minimize and overcome the unfavorable effects of these regimens, it is critical to identify innovative targets and test selective inhibitors of such targets. Major efforts are being made to develop small molecules against deregulated signaling pathways, which sustain T-ALL cell growth, survival, metabolism, and drug-resistance. This review will focus on recent improvements in the understanding of the signaling pathways involved in the pathogenesis of T-ALL and on the challenging opportunities for T-ALL targeted therapies.